Internacionalização da gestão ambiental: estudo de caso: Volvo do Brasil - Schiel, Theresa Christina de Carvalho Chaves (2010)
Environmental issues have been a growing concern as human beings moved to denser settlements. The use of natural resources increased significantly since the Industrial Revolution, with the consequent increase in ecological disruptions. From the seventies on, the implications of human development on the environment became the focus of discussions. In a globalized world where individuals move from country to country, go from local to global and modify the organization of social life as a result of cultural exchanges, a comparison among different environmental proposals and models becomes relevant. This comparison is essential for future managers to choose models or examples that are better adapted to each individual reality and that will bring higher returns, both economic and social, to their businesses. This study investigates the process of internationalization of environmental programs at a multinational corporation. The methodology adopted includes descriptive and exploratory research in the form of case studies. The study was developed at a multinational vehicle assembly plant based in Curitiba where managers of various departments, all with different attributions and willing to participate, were interviewed. A questionnaire and surveys were used and the results obtained met the objectives proposed, which confirms that the internationalization of environmental programs within a company helps raise the level of awareness and contributes to environmental education both in-house and in the community as a whole.